Immunization with the MipA, Skp, or ETEC_2479 Antigens Confers Protection against Enterotoxigenic E. coli Strains Expressing Different Colonization Factors in a Mouse Pulmonary Challenge Model - Hays, Michael P.; Kumar, Amit; Martinez-Becerra, Francisco J.; Hardwidge, Philip R. (Frontiers in Cellular and Infection Microbiology, 2016)
Achieving cross-protective efficacy against multiple bacterial strains or serotypes is an important goal of vaccine design. Enterotoxigenic Escherichia coli (ETEC) is an important cause of diarrheal disease in underdeveloped nations. We have been interested in identifying and characterizing ETEC antigens that generate protective immune responses independent of ETEC colonization factor (CF) expression. Our previous studies used proteomics to identify the ETEC MipA, Skp, and ETEC_2479 proteins as effective in protecting mice from homologous challenge with ETEC H10407 using a pulmonary inoculation model. This model permits analysis of mouse survival, bacterial clearance, and the production of secretory IgA (sIgA) and has been employed previously for studies of enteric pathogens for which robust oral challenge models do not exist. MipA belongs to a family of proteins involved in remodeling peptidoglycan. Skp rescues misdirected outer membrane proteins. ETEC_2479 is predicted to function as an outer membrane porin. These proteins are conserved in pathogenic ETEC strains as well as in commensal Proteobacteria. Antibodies produced against the ETEC MipA, Skp, and ETEC_2479 proteins also reduced the adherence of multiple ETEC strains differing in CF type to intestinal epithelial cells. Here we characterized the ability of 10 heterologous ETEC strains that differ in CF type to cause clinical signs of illness in mice after pulmonary challenge. ETEC strains C350C1A, E24377A, E7476A, WS2173A, and PE360 caused variable degrees of lethality in this mouse model, while ETEC strains B7A, WS6866B, 2230, ARG-2, and 8786 did not. Subsequent challenge experiments in which mice were first vaccinated intranasally with MipA, Skp, or ETEC_2479, when combined with cholera toxin, showed both that each antigen was protective and that protection was strongly correlated with fecal IgA concentrations. We conclude that the MipA, Skp, or ETEC_2479 antigens generate protection in the mouse pulmonary challenge model against ETEC strains that express different CFs.